Curves as a Media For Training (Cadre Skills in Anthropometric Measurements as a Preventive Measure For Stunting) - Winda Marchella Nurdin; Winda Novita Ramadhan; Regi Pebriana; Haipa Irdayanti; Gisha Amalia; Al Mukhlas Fikri (Jurnal EduHealth, 2024)
Skills in anthropometric measurements are one of the skills that every cadre must master and possess to monitor the growth and nutritional status of toddlers. This service activity aims to increase cadres' knowledge and skills in carrying out anthropometric height measurements that are easy to understand and apply in Posyandu activities. This activity is supported by an innovative height measuring tool that has been designed and is equipped with a pocket book and poster. The counseling technique was carried out using lecture and panel discussion methods to 32 cadres from 7 Posyandu, namely Posyandu Mekar Asih 1, Mekar Asih 2, Rido Asih, Fajar Sidik, Bahagia, Wargi Saluyu, and Rahayu. Based on the results of the paired parametric T comparative statistical test, it shows that there is no significant difference between the infantometer and the curve device (p > 0.05). however, there was a significant difference between the stadiometer and the Curve device (p < 0.05).